1993
DOI: 10.1302/0301-620x.75b3.8496206
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for lumbar spinal stenosis in old people

Abstract: We have reviewed 31 consecutive patients, aged 65 years or more, after surgical decompression for degenerative lumbar spinal stenosis. The average follow-up was 42 months. Assessment included a standard questionnaire, a pain diagram which was completed by the patient, and clinical and radiological examination. Patients were considered in three groups; degenerative spondylolisthesis (19), lateral recess stenosis (5), and central-mixed stenosis (7). The indication for surgery was leg pain: no patient had an oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
0
8

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 13 publications
6
58
0
8
Order By: Relevance
“…The ligamenta flava thicken, the facet joints hypertrophy, and a progressive disc degeneration results in a narrowing of the neural pathways. 21 Patients often present with a history of numbness, weakness, and radicular pain. Neural claudication is one of the key features, and it may be difficult to differentiate it from vascular impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The ligamenta flava thicken, the facet joints hypertrophy, and a progressive disc degeneration results in a narrowing of the neural pathways. 21 Patients often present with a history of numbness, weakness, and radicular pain. Neural claudication is one of the key features, and it may be difficult to differentiate it from vascular impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is slightly higher than that from the studies by Yukawa et al [9] and Gelalis et al [10] which was 7.1 and 7.5 respectively. Sanderson et al [11] reported a pre-operative pain score of 6.6 while Kwon et al The higher mean pain score in this study could be due to the advanced nature of the pathology in the population due to late presentation, and/or late acceptance of surgical treatment; as many of the patients refused spinal decompression until their pain became unbearable to them.…”
Section: Discussionmentioning
confidence: 51%
“…Twelve patients (30.8%) in this study had discectomy in addition to other procedures while in another study by Postacchini et al [15], discectomy was performed in 20% of the patients. Sanderson et al [11], however, reported that none of the 31 patients in their study with degenerative spinal stenosis had discectomy. Concomitant inter-transverse process fusion with autogenous bone graft was done in 30.8% of the patients, the figure is similar to 30% noted in the study by Postacchini et al [15], in contrast however, Sanderson et al [11], submitted that none of the patients who had decompression for degenerative lumbar spinal stenosis had fusion.…”
Section: Discussionmentioning
confidence: 85%
“…Generally, minor complications that do not prolong hospital stay make up the largest part [6,7,18,19,21,22]. The wide variation in complication rates is not only based on heterogeneity of patients, operative indications, and surgical procedures performed, but also on the varying definitions of complications per se.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed no higher rate of implant related complications in group 3 compared to group 1 and 2 ( Table 3). The probability for a reoperation appears to decrease with increasing age [8,13,21]. Outcomes described in the literature vary based on length of FU, patient selection, indications, and surgical procedures and present good to excellent results in 53-93% of cases [24].…”
Section: Discussionmentioning
confidence: 99%